Comparação de marcadores de estresse oxidativo em sangue, colostro e cordão umbilical após parto vaginal e cesáreo - Vendrame, Silmara Ana (2021)
Pregnancy is characterized as an oxidative event with physiological changes in the body to accommodate a developing fetus. The transition from pregnancy to the postpartum period can occur through different types of births, and the choice can considerably influence the level of oxidative stress generated. If birth occurs by vaginal delivery, labor may cause an intensification of reactive oxygen species production and a decline in the antioxidant system due to the constant change in oxygen pressure in the placental tissue during contraction, in addition to increased consumption of oxygen by skeletal and uterine musculature. Elective cesarean section, in turn, because it is programmed, does not involve labor and little is known about its oxidative effects. After birth, amid a scenario of oxidative changes, the mother starts to produce colostrum as a constant source of antioxidants that can protect newborns from attack by reactive species. In this context, this study aimed to compare markers of oxidative stress in maternal blood and in the umbilical cord immediately after vaginal delivery (VD) or cesarean (ECS), as well as to evaluate colostrum, seeking to identify the relationship between type of delivery and oxidative alterations. The study evaluating the blood was carried out at the University Hospital of Santa Maria with the participation of 76 pregnant women and their newborns, and the collection of maternal colostrum was carried out at the Casa de Saúde Hospital with the participation of 66 parturients. Oxidative damage was avaluated in maternal and fetal blood through quantification of thiobarbituric acid reactive substances (TBARS), advanced oxidation protein products (AOPP) and antioxidant defense through protein thiols groups (P-SH) and non-protein (NP-SH), the ferric reducing ability of plasma (FRAP), total antioxidant capacity (TAC) and catalase enzyme activity (CAT). The enzyme delta aminolevulinate dehydratase (δ-ALAD) was measured for the first time to our knowledge in the obstetric setting in maternal and fetal blood. In maternal colostrum, the nitrate/nitrite (NOx), AOPP, vitamin C, thiol groups and FRAP were evaluated. Through the obtained results, we can verify that there are differences in oxidative stress markers in different types of delivery. Mothers who underwent vaginal delivery showed greater oxidation and decreased antioxidant defenses compared to cesarean section. The type of delivery did not significantly alter the oxidative parameters in neonates and maternal colostrum. However, the antioxidant defenses were reduced in these groups when vaginal delivery was performed. In conclusion, vaginal delivery showed a greater change in oxidative stress parameters at the time and right after delivery, both in mothers and their newborns, and further studies are needed to assess the effects on health throughout life. A diet rich in antioxidants can be encouraged, especially for pregnant women planning to have a vaginal birth.